COVID-19 and Quitting Jobs - Demirkaya, Harun; Aslan, Mustafa; Güngör, Habibe; Durmaz, Vildan; Rodoplu Şahin, Didem (Frontiers in Psychology, 2022)
Despite substantial studies on COVID-19 and the problems employees face, the association between COVID-19 and resigning jobs has not caught the interest of researchers. Millions have already resigned from their employment, and more are expected to resign. This study aims to investigate the relationship between the demographics of employees, the course of COVID-19, perceived effect of COVID-19 on life (PEoC), fear, entrapment feeling, depression, and quitting the job during the COVID-19 pandemic. A cross-sectional study was designed, and a convenient sampling method was adopted. Data were collected via an online questionnaire and analyzed by using SPSS version 26. Correlation and regression analyses were performed to reveal the relationship. Coefficients and significance values were used to interpret the results. Independent samples t-test and one-way ANOVA are used to determine the difference across the groups. The correlation between depression and work location is statistically significant. The PEoC increases fear, internal and external entrapment, and depression. Despite the statistically significant correlations between quitting jobs and the education level, internal and external entrapment, PEoC, fear, and depression for employees who have COVID-19 history, quitting the job was found to be affected only by COVID-19 history, internal entrapment feeling, and education level. This study has shown that quitting the job is associated with PEoC, depression, and internal and external entrapments. The correlation between quitting jobs and other conditions differs depending on the COVID-19 history of the employee. Furthermore, quitting the job is being affected by the coronavirus history, the internal entrapment, and education level.